Analysis of The Effect of Business Strategy on The Quality of Management Accounting Information Systems - Ayke Nuraliati; Twenty Selvia Sari Sianturi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
Management accounting information system (SIAM) is used as a tool to produce financial and non-financial / management accounting information that is used to assist executive managers or internal parties in planning resource allocation, supervision, evaluation, and performance evaluation, both financial performance and non-financial performance including managerial performance and employee performance. Management accounting information systems refer to normative matters, but when management accounting information systems are implemented it has unexpected or unexpected consequences so that it can affect the satisfaction of users of information systems, this is because in the context of the organization and socially not well understood by users. This research was conducted on general insurance in Bandung where the respondents were operational managers using an explanatory survey method. Testing data using simple regression The results of research on insurance companies in Bandung found that business strategies affect the quality of management accounting information systems